2013
DOI: 10.1179/1351000213y.0000000075
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload as a major targetable pathogenesis of asbestos-induced mesothelial carcinogenesis

Abstract: Few people expected that asbestos, a fibrous mineral, would be carcinogenic to humans. In fact, asbestos is a definite carcinogen in humans, causing a rare but aggressive cancer called malignant mesothelioma (MM). Mesothelial cells line the three somatic cavities and thus do not face the outer surface, but reduce the friction among numerous moving organs. MM has several characteristics: extremely long incubation period of 30-40 years after asbestos exposure, difficulty in clinical diagnosis at an early stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…p16 INK4a /p14 ARF deletion was also detected in rat peritoneal mesotheliomas established by repeated injection with iron saccharate and an iron chelator, NTA [72]. As iron is crucially involved in both models, the similarity between fiber and ironinduced carcinogenesis again highlights the significance of iron overload and oxidative stress in the underlying genomic alterations that occur so frequently in these malignancies [62,73].…”
Section: Asbestos-induced Genomic Alterationsmentioning
confidence: 75%
“…p16 INK4a /p14 ARF deletion was also detected in rat peritoneal mesotheliomas established by repeated injection with iron saccharate and an iron chelator, NTA [72]. As iron is crucially involved in both models, the similarity between fiber and ironinduced carcinogenesis again highlights the significance of iron overload and oxidative stress in the underlying genomic alterations that occur so frequently in these malignancies [62,73].…”
Section: Asbestos-induced Genomic Alterationsmentioning
confidence: 75%
“…More than one fourth of the cases were diagnosed microscopically only during autopsy indicating that the diagnostics of MPeM are quite demanding due to the disease's long latency period and obscure symptoms [8,16]. In addition our results indicate that more than half of the MPeM cases had spread beyond the regional lymph nodes at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…(6) Irrespective of the types of asbestos, postadministration of nitrilotriacetate (NTA; iron chelating agent to promote the Fenton reaction) (11,12) significantly shortened the periods of carcinogenesis, confirming the major role of iron in this process. (13,14) In the case of chrysotile, which does not include iron in itself, its hemolytic activity and the subsequent adsorption of hemoglobin were important, (15) in addition to the general affinity of asbestos to histones. (16) We also reported that i.p.…”
mentioning
confidence: 99%